AN INTEGRATED GEOMECHANICAL STUDY OF POST-DRILLING - Saktyanto S, Yoga
Mechanical state of the rock formation is in the state of equilibrium before the rock formation being drilled. After drilling, the rock surrounding the wellbore undergoes stress field alteration as the rock is removed. Chemical reactions also occur due to interaction between rock formation and drilling fluid. Under these conditions, the rock surrounding the wellbore can become unstable, begin to deform, fracture, cave into the wellbore or dissolve into the drilling fluid. Such changes can generate hole problems that impact drilling operation and can result in increasing operating cost related to Non-Productive Time (NPT) and unexpected cost expenditures combating wellbore instability problems. This study presents an integrated geomechanical analysis methodology involved, as well as, the main geomechanical issues that were considered in the well planning stage. Hole problems analysis is determined by reviewing all drilling problems that occurred during the drilling operations (post-drilling analysis). From this study, drilling hazard for each formation lithology section of the field were generated. Mitigation plan and recommendation comprise of drilling methods, casing setting depth, basic drilling fluid analysis, and rock formation analysis were generated. Such information are essential for planning future drilling operation to mitigate hole problems. Performing integrated geomechanical study of post-drilling can provide important knowledge of rock formation behavior, thus drilling hazard and lesson learned can be identified. Drilling hazards can be reduced by determining the proper casing setting depth. Casing setting depth determination requires accurate pore and fracture pressure. Geomechanical studies are needed to estimate pore and fracture pressure accurately. Beside pore and fracture pressure, the formations to be drilled themselves are also influencing the casing setting depths determinations. Without integrated knowledge of geomechanics, it is less likely to set the casing fit the purpose. Before drilling operation, geomechanical study is the most essential analysis to generate mitigating strategy. Without a strategy for mitigating or minimizing potential geomechanical problems, drilling operations may cost millions more than budgeted. Identifying potential issues, planning for and managing them can saves drilling operation time, improves safety at the well site, and also reduce well cost.